CIDADANIA E AGRICULTURA FAMILIAR:UMA QUESTÃO DE TRATAMENTO (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
“With the intention of participating in the “XI Brazilian Congress of Collective Process and Citizenship”, the “75th Legal Week”, by Unaerp, and attentive to the theme “Confronting Inequalities in Contemporary Life”, through this article, under the title ““Citizenship and Family Farming: A Question of Treatment””, the aim is to present the concepts, principles and purposes prescribed by Law 11,326/2,006, which established the National Family Farming Policy, but, above all, taking into account the issues social, environmental, political, economic and legal, highlight the main achievements of rights and citizenship and the biggest challenges in combating inequalities among indigenous peoples, extractivists, quilombolas, foresters, artisanal fishermen and family farmers, in the academic-scientific, political- legal and professional”. “Keywords: Citizenship – Indigenous – Extractivists – Quilombolas – Fishermen;”